2010
DOI: 10.1208/s12248-010-9237-6
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular Tightness and Claudin-5 Expression is Increased in the BCEC/Astrocyte Blood–Brain Barrier Model by Increasing Media Buffer Capacity During Growth

Abstract: Abstract. Most attempts to develop in vitro models of the blood-brain barrier (BBB) have resulted in models with low transendothelial electrical resistances (TEER), as compared to the native endothelium. The aim of the present study was to investigate the impact of culture pH and buffer concentration on paracellular tightness of an established in vitro model of the BBB consisting of bovine brain capillary endothelial cells (BCEC) co-cultured with rat astrocytes. BCEC and rat astrocytes were isolated and cocult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 40 publications
1
52
1
Order By: Relevance
“…Important cues for cell proliferation are provided by the extracellular matrix such as integrin and growth factor (bFGF) activation 49 . Buffer concentration and pH of the culture media have been described to impact positively on paracellular tightness 50 and we observed a better reproducibility between cultures with the addition of HEPES buffer at 5 mM.…”
Section: Other In Vitro Bbb Models Based On Endothelial Cells From Rasupporting
confidence: 62%
“…Important cues for cell proliferation are provided by the extracellular matrix such as integrin and growth factor (bFGF) activation 49 . Buffer concentration and pH of the culture media have been described to impact positively on paracellular tightness 50 and we observed a better reproducibility between cultures with the addition of HEPES buffer at 5 mM.…”
Section: Other In Vitro Bbb Models Based On Endothelial Cells From Rasupporting
confidence: 62%
“…STX100C) and hence better reproducibility. The "Endohm" chamber system with large plate electrodes to fi t in the fi lter cup (above) and the well (below) the cells on the fi lter, samples a larger area of membrane including the more uniform central area, and can give more reproducible readings (Cohen-Kashi Malina et al 2009 ;Helms et al 2010Helms et al , 2012Patabendige et al 2013a , b ); however, the "plunger" action of inserting the upper electrode can disturb the cells, particularly the brain endothelial cells, which are much thinner and more fragile than the CNS barrier epithelial cells.…”
Section: Methods To Measure Barrier Permeability and Teermentioning
confidence: 99%
“…The general TEER levels in these models have ranged from approximately 100-800 Ω·cm 2 , which is reasonably tight compared to other models. However, we previously demonstrated that TEER across a bovine endothelial/rat astrocyte co-culture BBB model was raised approximately two-fold by culture in highly buffered differentiation medium reaching values above 1,600 Ω·cm 2 [32]. Low TEER in cell culture models may cause lack of polarized transport because of a large paracellular flux contributing to the overall transport of the substrate [28].…”
Section: Polarized Transport Of Efflux Transporter Substrates May Bementioning
confidence: 99%
“…Recently, our group published a new culture protocol based on the model published by Gaillard et al [31] to improve the tightness of a bovine endothelium/rat astrocyte BBB model [32,33]. The co-cultured endothelial cells displayed high TEER values, low mannitol fluxes, and polarized transport of the small molecules, L-glutamate and L-aspartate favouring the abluminal-to-luminal direction [34].…”
Section: Introductionmentioning
confidence: 99%